Rancang Bangun Sistem Informasi Geografis Rumah Tidak Layak Huni Sebagai Pendukung Keputusan Kebijakan Di Tingkat Desa - Julian Chandra Wibawa; Bella Hardiyana (Maranatha University Press, 2019)
The implementation of social welfare development programs in developing countries is generally focused on the empowerment program of the poor, which is more nuanced in a participatory approach involving the community, business and government. empowerment is considered appropriate to be one of the policy choices in the development of social welfare today. The development of social welfare based on the principle of empowerment is intended that in the handling of the poor, it must be done through increasing the capacity of human resources to increase independence (Law Number 13 of 2011). Regional development has an impact on national development. Poverty reduction policies realized through community empowerment programs have become the main agenda and prior development in Baleendah Subdistrict, especially Rancamanyar Village. One of the poverty alleviation programs through community empowerment carried out in Rancamanyar Village is the Housing Assistance Program for uninhabitable houses. Various local government efforts to reduce the number of uninhabitable houses are still considered uneven. With the limited management and processing of survey data in the regions, it is one of the factors that do not help the existing policies. With the construction of a geographic information system for uninhabitable homes, one of the efforts that must be taken by the local government in order to support and assist in making decisions for uninhabitable houses is to conduct geographical analysis and mapping of uninhabitable houses in Rancamanyar Village, so that help is not the wrong target.